Pengaruh Efektivitas Sistem Informasi Akuntansi pada Kinerja Karyawan dengan Insentif dan Motivasi Kerja sebagai Pemoderasi - Prariadena, Chandrika Hutami; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi, 2019)
This study aims to determine the effect of the effectiveness of accounting information systems on employees’ performance with incentives and work motivation as moderators in Denpasar LPD. The population of this study was employees at the 35 LPDs in Denpasar. The sample was determined by using a purposive sampling method with a total sample of 99 people. The methods of data collection were done by using questionnaire method and simple linear regression data analysis techniques and moderation regression analysis. Based on the results of the analysis found that the effectiveness of accounting information systems have positive effects on employees’ performance such as incentives weaken the effectiveness of accounting information systems on employee performance and work motivation reinforces the effectiveness of accounting information systems on employee performance in Denpasar LPD. Keywords : Effectiveness of accounting information systems, incentives, work motivation employee performance